Pengaruh Dukungan Sosial terhadap Motivasi Hidup Orang Dengan HIV atau AIDS (ODHA) di Provinsi Kalimantan Tengah - Nurul Chusna; Nurhalina Nurhalina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The cumulative number of HIV & AIDS in Central Kalimantan Province continues to increase where in 2017 there were 807 reported cases. Based on observations of the situation faced by people with HIV & AIDS is very complex, in addition to having to deal with their own disease, they also face stigma and discrimination that affects the low motivation of patients' lives. Most sufferers experience physical, psychological and social problems that require comprehensive interventions (medical, nutrition, social support and psychotherapy/counseling. The purpose of this study is to determine the effect of social support on the motivation of living ODHA in Central Kalimantan Province. This type of research is an observational study with a cross-sectional study approaching. Results of research conducted on life motivation from participants obtained extrinsic motivation and intrinsic motivation themes Social support received by people with HIV / AIDS Participants have the same view that they get various forms of social support. And the following forms social support that researchers obtained from interviews with participants formed in the themes, namely physical support, emotional support, security support, skills support, social support and economic support Source of social support obtained by people with HIV / AIDS. In this study, the theme was obtained sources of external support and internal support sources. Four social themes are expected by HIV / AIDS sufferers. The theme is facilities to meet economic needs, health facilities, health support and community views of people with HIV / AIDS positive.